PENGARUH PROMOSI, HARGA, KEPUASAAN, DAN KUALITAS PRODUK TERHADAP LOYALITAS PELANGGAN E-COMMERCE TOKOPEDIA DI PT. MITRA ANDA SURAKARTA - Feriza Dinda Ardhana; Santosa Tri Prabawa; Dian Noor Citra Perdana (JURNAL ILMIAH EDUNOMIKA, 2025)
the purpose of the study was to determine the effect of promotion, price, satisfaction, and product quality on customer loyalty of tokopedia e-commerce at pt. Mitra anda surakarta. the type of research that the author uses in the study is a quantitative descriptive method. the population of this study is all tokopedia e-commerce customers at pt. mitra anda surakarta. the sampling method used in this study uses non-probability sampling with accidental sampling techniques. the sample obtained was 96 people. data collection used in this study was using documentation and personal questionnaires. data analysis techniques used descriptive statistical tests, research instrument tests, classical assumption tests and hypothesis testing. the software used in this analysis is spss 23. this study can be concluded as follows: there is no effect of promotion on tokopedia e-commerce customer loyalty at pt. mitra anda surakarta. there is an effect of price on tokopedia e-commerce customer loyalty at pt. mitra anda surakarta. there is an influence of satisfaction on the loyalty of tokopedia e-commerce customers at pt. mitra anda surakarta. there is an influence of product quality on the loyalty of tokopedia e-commerce customers at pt. mitra anda surakarta.there is a joint influence of promotion, price, and satisfaction on the loyalty of tokopedia e-commerce customers at pt. mitra anda surakarta. Keywords : promotion, price, satisfaction, product quality, customer loyalty, e-commerce.